2010
DOI: 10.1007/s11356-010-0396-x
|View full text |Cite|
|
Sign up to set email alerts
|

The OECD validation program of the H295R steroidogenesis assay: Phase 3. Final inter-laboratory validation study

Abstract: Based on the results obtained during this validation study and the accordingly revised test protocols, an OECD draft test guideline was developed and submitted to the OECD working group of the national coordinators of the test guidelines program (WNT) for comments in December 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 42 publications
2
61
0
Order By: Relevance
“…PBO was tested for (anti-)estrogenic and (anti-)androgenic effect in the OECD-standardized H295R steroidogenesis in vitro assay (Hecker et al 2011). PBO tested negative for E2 production with 100 µM as the highest tested concentration and the LOEC for testosterone production was 10 mg/l (30 µM).…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…PBO was tested for (anti-)estrogenic and (anti-)androgenic effect in the OECD-standardized H295R steroidogenesis in vitro assay (Hecker et al 2011). PBO tested negative for E2 production with 100 µM as the highest tested concentration and the LOEC for testosterone production was 10 mg/l (30 µM).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…In vitro studies have demonstrated that PBO affects steroidogenesis (Hecker et al 2011). Non EATS-modalities were also demonstrated in vitro as PBO showed immunotoxicity (Battaglia et al 2010) and a negative effect on the release of corticotropin (Luini and Axelrod 1985).…”
Section: Piperonyl Butoxidementioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the single pesticides and the two pesticide mixtures on the production of progesterone, testosterone, and estradiol were tested in the NCI-H295R human adrenocortical carcinoma cell line (ATCC no. CRL-2128, LGC Standards, Boras, Sweden) as previously described (Hecker et al, 2011). In brief cells were seeded in 24-well culture plates (Costar3524,Corning,NY, USA) with DMEM/F12 medium (Gibco, Paisley, UK) supplemented with 2.0% Nu-serum (BD Sciences Denmark) along with 1% ITS+ premix (containing6.25 μg/ml insulin, 6.25 μg/ml transferrin,6.25 ng/ml selenium,1.25 mg/ml BSA and 5.35 μg/ml linoleic acid; BD Sciences Denmark) and incubated for 24 h at37°C in a humidified atmosphere of 5% CO2/air.…”
Section: H295r Assaymentioning
confidence: 99%
“…These assays serve as first-tier screens to identify the potential EDC activity and suggested MOA of man-made chemicals detected in the environment (Hecker et al, 2011). Although the recombinant yeast assay (using hAR) has not been included in the battery of first-tier tests suggested by the USEPA, the YAS has been recognised as an assay that it is a relatively inexpensive screening tool with a standardised protocol (Sohoni and Sumpter, 1998;De Jager et al, 2011;Kolle et al, 2011).…”
Section: Introductionmentioning
confidence: 99%